Pengaruh Transaksi, Akurasi Keuangan dan Kinerja Keuangan Terhadap Pencapaian Pendapatan UMKM dalam Penggunaan Aplikasi QRIS - Audri Depitasari (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2025)
The development of digital payment systems has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt the Quick Response Code Indonesian Standard (QRIS) as a cashless payment method. However, the use of QRIS is not only related to transaction convenience but also affects financial management and income achievement of MSMEs. This study aims to analyze the effect of transactions, financial accuracy, and financial performance on MSMEs’ income achievement in the use of QRIS applications. This research employs a quantitative approach using a survey method. Data were collected from 70 MSME respondents who use QRIS through questionnaires measured using a Likert scale. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that transactions, financial accuracy, and financial performance partially have a positive and significant effect on MSMEs’ income achievement. Furthermore, the simultaneous test results show that all independent variables jointly have a significant effect on MSMEs’ income achievement. This study concludes that the optimal use of QRIS can enhance MSMEs’ income by improving transaction efficiency, financial recording accuracy, and overall financial performance. Keywords:. QRIS; Transactions; Financial Accuracy; Financial Performance; MSME Revenue